Content Curation, Evaluation, and Refinement on a Nonlinearly Directed Imageboard: Lessons From Danbooru. (November 2019) - Britt, Brian C.
While linearly directed imageboards like 4chan have been extensively studied, user participation on nonlinearly directed imageboards, or "boorus, " has been overlooked despite high activity, expansive multimedia repositories with user-defined classifications and evaluations, and unique affordances prioritizing mutual content curation, evaluation, and refinement over overt discourse. To address the gap in the literature related to participatory engagement on nonlinearly directed imageboards, user activity around the full database ofN = 2, 987, 525 submissions to Danbooru, a prominent nonlinearly directed imageboard, was evaluated using regression. The results illustrate the role played by the affordances of nonlinearly directed imageboards and the visible attributes of individual submissions in shaping the user processes of content curation, evaluation, and refinement, as well as the interrelationships between these three core activities. These results provide a foundation for further research within the unique environments of nonlinearly directed imageboards and suggest practical applications across online domains.